Politeness Principles in Written Conversations: An Analysis of English Textbook - Nur Azmi Laila; Sugirin Sugirin (STAI Hubbulwathan Duri, 2022)
This study aims to identify kinds of maxims of politeness principles used in written conversation in the English textbook for tenth-grade students. This study uses a qualitative design. This is descriptive qualitative research. The data is collected from written conversations in the English textbook for the tenth-grade students. To analyse the data, the researcher used Geoffrey Leech’s politeness principles theory,which consists of six maxims. The data results show that there is a tact maxim, three generosity maxims, fourteen approbation maxims, four modesty maxims, two agreement maxims, and five sympathy maxims. The total data are twenty-nine. For the textbook produced by the government that uses the 2013 curriculum, which is concerned with character education, it should be the number of maxims of politeness to be found in the textbook's written conversation.